Cheiloscopy: The Study of Lip Prints in Sex Identification between Indian and Malaysian Population - Nurul Afiqah Amani Binti Zaaba1, Gheena.S2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: The study of lip prints, is commonly applied in forensic odontology and it is known as cheiloscopy. The term cheiloscopy was derived from Greek words, in which “cheilos” means lip and “scopy” means to examine. In general, cheiloscopy is define as a method of identifying an individual based on the arrangement of lines seen on the red part of the lips or a science dealing with the various line appearing on the red part of the lips. The pattern of wrinkles and grooves that are present on the lips has distinct characteristic features of an individual which are almost similar to the fingerprints. It also will not change throughout the life. Therefore, it can be used for personal identification and sex determination.Aim: To investigate lip print pattern in males and females and to evaluate them between Malaysian and Indian population.Materials and Method: There were 40 participants of both gender. 20 of them are from the Malaysian population and another 20 people are from the Indian population. Each participant was instructed to clean their lips with a clean white cloth, before taking the lip print. This was followed by the application of dark coloured lip stick on lips by using the lip stick applicator. Cellophane tape was used to take the negative impression of the lip pattern. The glued portion of the cellophane tape was placed on the lips by giving a light pressure beginning from the centre of the lips till the corner of the mouth. Then, the impression was transferred to a clean white paper and seen under the magnifying glass.Results: Type I lip pattern was commonly seen in Indian population, followed by type III, II and IV. Whereas for Malaysian population, type III was most common followed by type I, II and IV. There was significant difference between both population. In this study, it showed that type I was the most common lip print pattern seen in both Indian and Malaysian population for females. Whereas for male, type III was more common in Malaysian population, and both type III and IV were more common in Indian population.Conclusion: There was no significant difference in both population according the general distribution of lip print pattern. There was no correlation or similarity of lip print patterns between each participants in both population. Thus, cheiloscopy can be used for sex determination and also personal identification.